COMPETITION BETWEEN LIGHT CLUSTER AND CONSTITUENT MULTINUCLEON EMISSION IN HEAVY-ION REACTIONS - Xenoulis, A. C. (HNPS Advances in Nuclear Physics, 2020)
Isoproduct competition. i.e. competition between cluster and multlnucleon emission leading to the same residual nucleus, emerges as a general, interesting and useful characteristic of nuclear reactions. Common properties and factors underlying the competition between pn and d as well as between p2n. dn and t evaporation are recognized and discussed. The application of the isoproduct-competition method in the delineation of the mechanisms involved in 7Li-lnduced reactions suggests that an additional mechanism, breakup-fusion, is involved even at very low energies. Finally, the competition associated with alpha emission In the 12C+16O reaction demonstrates a strong contribution from composite 4He emission which cannot be accounted far by either the systematica or standard statistical calculations.